2020
DOI: 10.1002/ab.21889
|View full text |Cite
|
Sign up to set email alerts
|

Sexual objectification increases retaliatory aggression

Abstract: Two experiments were conducted to investigate whether sexual objectification increases retaliatory aggression serially through increased vulnerability and hostile intent attributions. Female participants were first exposed to the sexual objectification manipulation by receiving compliments from an online male partner (Experiment 1) or imagining a workplace objectification experience (Experiment 2). Afterward, their vulnerability and hostile intent attributions were assessed. Finally, they were given an opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 112 publications
(136 reference statements)
2
2
0
Order By: Relevance
“…For what concerns sexual objectification, our findings clearly suggest that female targets of sexual objectification react following two distinctive emotional and behavioural paths. Indeed, our findings concur with the apparently divergent literature that sometimes reported increased shame 4 , 6 9 and sometimes increased anger/disgust in sexually objectifying contexts 20 , 25 , 26 ; at the same time these contexts sometimes elicited active 18 , 25 , 26 and sometimes passive actions 5 , 14 16 towards the objectifying men. The present findings suggest that female targets of sexual objectification generally experience anger/disgust and actively respond to the perpetrator, punishing him.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For what concerns sexual objectification, our findings clearly suggest that female targets of sexual objectification react following two distinctive emotional and behavioural paths. Indeed, our findings concur with the apparently divergent literature that sometimes reported increased shame 4 , 6 9 and sometimes increased anger/disgust in sexually objectifying contexts 20 , 25 , 26 ; at the same time these contexts sometimes elicited active 18 , 25 , 26 and sometimes passive actions 5 , 14 16 towards the objectifying men. The present findings suggest that female targets of sexual objectification generally experience anger/disgust and actively respond to the perpetrator, punishing him.…”
Section: Discussionsupporting
confidence: 91%
“…Still, those women who self-objectify more, also experience more shame emotions and punish the perpetrator less. The increased punishment behaviour in female targets of sexual objectification is consistent with previous studies in which objectified women reported higher willingness to activism 26 , or increased explicit aggressive behaviours 18 . More generally, anger responses are typically related to aggressive behaviours 23 or direct aggression 50 , making it reasonable that women act in this way when they experience anger during an objectifying social interaction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations